O Programa Bolsa Família, o “efeito preguiça” e o mercado de trabalho - Prósperi, Luciene De Oliveira (2015)
A recurring criticism of the Bolsa Família Program (PBF, in Portuguese) in public opinion is the suspicion that its beneficiaries would opt to work less than they would work if they did not receive the cash transfer. This suspicion is commonly called “laziness effect”. The present study is a literature review investigating the reality of this effect and how the program deals with its possibility. The thesis begins analyzing the beneficiary’s profile and the empirical literature on the laziness effect. After that it offers a contextualization of the labor market for the poorer individuals and details PBF as part of the Brasil Sem Miséria Plan (BSM, in Portuguese), which includes many actions directed at promoting productive inclusion, a way to avoid the supposed laziness effect. Besides the introduction and the conclusion sections, the thesis has three chapters. Following the introduction, where the research question is delineated in greater detail, the first chapter reviews the most important econometric literature on the relation of the PBF’s beneficiaries with the labor market. In general, the reviewed works did not find evidences of the laziness effect – or only very small effects on some indicator of some subpopulation, e.g. a small reduction on the number of work hours of mothers. Another result of the first chapter is the realization that the econometric studies offer scarce information on the jobs available to the poor, and extremely poor, people. Without this knowledge it is impossible to adequately comprehend the beneficiaries’ work seeking behavior. In view of this, the second chapter dedicates itself to a more sociological task: the contextualization of the job market for poorer people, including themes such as informality, outsourcing, microentrepreneurship, and degrading jobs or slave-like conditions. The last chapter describes in detail the PBF’s structure and functioning as a part of BSM, emphasizing the carefulness and complexity of its design. BSM includes many actions to promote productive inclusion as a guarantee that the families will be able to have an income from a non-degrading job. This chapter ends presenting how PBF guarantees to the beneficiaries that get into the formal sector a way of returning to the program if necessary, another way of avoiding the laziness effect. Thus the study concludes that the PBF do not reduce the proneness to work in any important measure. Above this, the study emphasizes that the question must be analyzed taking into consideration the facts that (a) social protection is a right, that (b) the labor market for the poorer is inadequate in many senses and that (c) the BSM already has many actions promoting the productive inclusion of its beneficiaries.